Advanced Computer and Communication Engineering Technology Proceedings of ICOCOE 2015 - Sulaiman, Hamzah Asyrani; Othman, Mohd Azlishah; Othman, Mohd Fairuz Iskandar; Rahim, Yahaya Abd; Pee, Naim Che (Lecture Notes in Electrical Engineering, 2016)
This book covers diverse aspects of advanced computer and communication engineering, focusing specifically on industrial and manufacturing theory and applications of electronics, communications, computing and information technology. Experts in research, industry, and academia present the latest developments in technology, describe applications involving cutting-edge communication and computer systems, and explore likely future trends. In addition, a wealth of new algorithms that assist in solving computer and communication engineering problems are presented. The book is based on presentations given at ICOCOE 2015, the 2nd International Conference on Communication and Computer Engineering. It will appeal to a wide range of professionals in the field, including telecommunication engineers, computer engineers and scientists, researchers, academics and students.